Experimental and kinetic modeling study of the oxidation of cyclopentane and methylcyclopentane at atmospheric pressure. Issue 12 (7th August 2020) - Dayma, G.; Thion, S.; Serinyel, Z.; Dagaut, P.
Abstract: Cyclopentane and methylcyclopentane oxidation was investigated in a jet‐stirred reactor at atmospheric pressure, over temperatures ranging from 900 to 1250 K, for fuel‐lean, stoichiometric, and fuel‐rich mixtures at a constant residence time of 70 ms. The initial mole fraction of both fuels was kept constant at 1000 ppm. The reactants were highly diluted by a flow of nitrogen to ensure thermal homogeneity. Samples of the reacting mixture were analyzed online and off‐line by Fourier transform infrared spectroscopy and gas chromatography. A detailed kinetic mechanism consisting of 590 species involved in 3469 reactions was developed, and simulation results were compared to these new experimental data and previously reported ignition delays. Reaction pathways analysis as well as sensitivity analyses were performed to get insights into the differences observed during the oxidation process of cyclopentane and methylcyclopentane.